Cell-loaded carboxymethylcellulose microspheres sustain viability and proliferation of ATDC5 cells. (5th November 2018) - Ke, Yu; Liu, Caikun; Wang, Yanting; Xiao, Meng; Fan, Jiachen; Fu, Pengcheng; Wang, Shuhao; Wu, Gang
Abstract: Cell-loaded carboxymethylcellulose (CMC) microspheres were generated via a flow focusing microfluidic device, with a final aim to obtain viable ATDC5 aggregates with sustained proliferation capacity. We synthesized various CMC with phenolic groups (CMC-Ph) and demonstrated that high CMC-Ph molecular weight, high CMC-Ph concentration (>0.8 g/ml) or long culturing period had obvious inhibition effect on ATDC5 proliferation, but low horseradish peroxidase concentration (HRP, <0.4 mg/ml) did not. CMC-Ph gels being obtained through HRP/H2 O2 reaction showed an enhancing strength and decreasing break stain as the molecular weight of CMC-Ph increased, along with a decreasing gelation time. The microfluidics-based synthesis of cell-loaded microspheres with great design flexibilities was achieved using CMC-Ph with weight-average molecular weight of 1.0 × 10 5 . ATDC5 cells were viable up to 41 days of culture and proliferated gradually with increasing culture time. High cell density in CMC-Ph solution and high fetal bovine serum concentration in culture medium were prone to forming cell aggregates. Isolated cells from the microspheres showed the typical spherical morphology of undifferentiated ATDC5. Therefore, CMC-Ph microspheres might be used as cell aggregates depots to study cell-cell or cell-biomaterials functions for tissue engineering applications. Graphical Abstract: